Neuroprotective and neurotrophic effects of Lanthionine Ketimine Ester. (18th January 2018) - Marangoni, Natalia; Kowal, Kathy; Deliu, Zane; Hensley, Kenneth; Feinstein, Douglas L.
Highlights: Lanthionine ketimine ethyl ester (LKE) reduces cell death in human SH-SY5Y cells and primary mouse cerebellar granule cells. LKE reduces glutamate- induced cell death and reactive oxygen species production. LKE increases neuronal process numbers and lengths. Reported beneficial actions of LKE in vivo may involve direct actions on neurons as well as suppression of inflammatory responses. Abstract: Lanthionine ketimine ethyl ester (LKE) is a synthetic derivative of the naturally occurring amino acid lanthionine ketimine. We previously showed that LKE reduced clinical signs in a mouse model of multiple sclerosis (MS) associated with reductions in axonal damage; however, whether LKE has direct beneficial actions on mammalian neuronal cells was not examined. In the current study, we tested the effects of LKE in SH-SY5Y human neuronal cells and in primary mouse cerebellar granule neurons. In both cell types, LKE dose-dependently reduced the cell death that occurred spontaneously followed a change in media. LKE also reduced cell death due to glutamate excitoxicity, accompanied by a reduction in production of reactive oxygen species. LKE induced neuritogenesis in both undifferentiated SH-SY5Y cells and in primary neuron, increasing process numbers and lengths. These results demonstrate that direct neuroprotective and neurotrophic effects of LKE likely contribute to its beneficial actions in vivo.